Compact four‐port MIMO antenna on slotted‐edge substrate with dual‐band rejection characteristics - Raheja, Dinesh Kumar; Kanaujia, Binod Kumar; Kumar, Sachin (International journal of RF and microwave computer-aided engineering, 2019)
A compact ultra‐wideband (UWB) multiple‐input‐multiple‐output (MIMO) antenna with dual band elimination characteristics is presented. The proposed MIMO antenna is comprised of four identical elliptical shaped monopole radiators located orthogonally to each other. A second order Koch fractal geometry is applied on the edges of the ground planes of the radiating elements; to reduce the overall size of the MIMO antenna, without compromising the lower frequency response. Further, in order to eliminate the undesired resonant bands (3.5 and 5.5 GHz) from UWB, an elliptical complementary split ring resonator is introduced in the monopole radiator. For reducing inter‐element coupling in the proposed MIMO antenna, a different approach (of slotted edge substrate) is used, as a substitute of traditional decoupling stub/elements. In the entire operating band of 3 to 13.5 GHz, inter‐element isolation more than 22 dB and envelope correlation coefficient less than 0.008 are obtained. The measured parameters of the fabricated prototype antenna are found in good agreement with the simulated results.